Manipulating the immune system for anti-tumor responses and transplant tolerance via mixed hematopoietic chimerism - Gibbons, Carrie; Sykes, Megan (Immunological reviews, 2008)
Stem cells (SCs) with varying potentiality have the capacity to repair injured tissues. While promising animal data have been obtained, allogeneic SCs and their progeny are subject to immune-mediated rejection. Here, we review the potential of hematopoietic stem cells (HSCs) to promote immune tolerance to allogeneic and xenogeneic organs and tissues, to reverse autoimmunity, and to be used optimally to cure hematologic malignancies. We also review the mechanisms by which hematopoietic cell transplantation (HCT) can promote anti-tumor responses and establish donor-specific transplantation tolerance. We discuss the barriers to clinical translation of animal studies and describe some recent studies indicating how they can be overcome. The recent achievements of durable mixed chimerism across human leukocyte antigen barriers without graft-versus-host disease and of organ allograft tolerance through combined kidney and bone marrow transplantation suggest that the potential of this approach for use in the treatment of many human diseases may ultimately be realized.